1990
DOI: 10.1152/ajprenal.1990.258.4.f992
|View full text |Cite
|
Sign up to set email alerts
|

Effect of specific amino acid groups on renal hemodynamics in humans

Abstract: The effect of specific amino acid groups on renal hemodynamics was examined in seven healthy young volunteers. Each subject received a 3-h intravenous infusion according to one of the following protocols: study 1, gluconeogenic amino acids (Arg, Gly, Pro, Cys, Met, Ser); study 2, alanine alone; study 3, branched-chain amino acids (BCAA, Leu, Ile, Val); or study 4, 0.9% saline. The rise (40-60% above base line) in total plasma amino acid concentration was similar in studies 1-3; no change was observed in study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 0 publications
2
20
0
1
Order By: Relevance
“…We detected no change in the urea excretion rate, urea filtered load or plasma glucagon/insulin ratio and, furthermore, the observed decrease in plasma ornithine levels (and corresponding increase in plasma arginine levels) induced by the EAA infusion could be interpreted as indicating reduced ureagenesis. Our data are in line with the demonstration that GFR does not increase after administration of D-serine and cystine [2] or branched-chain AA [3][4][5] which are all AA that are not metabolized in the splanchnic region, whereas GFR is stimulated by a mixture of gluconeogenetic AAs [3].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We detected no change in the urea excretion rate, urea filtered load or plasma glucagon/insulin ratio and, furthermore, the observed decrease in plasma ornithine levels (and corresponding increase in plasma arginine levels) induced by the EAA infusion could be interpreted as indicating reduced ureagenesis. Our data are in line with the demonstration that GFR does not increase after administration of D-serine and cystine [2] or branched-chain AA [3][4][5] which are all AA that are not metabolized in the splanchnic region, whereas GFR is stimulated by a mixture of gluconeogenetic AAs [3].…”
Section: Discussionsupporting
confidence: 91%
“…A number of clues indicate that this intermediate step may occur in the splanchnic region. Branchedchain AA, which are poorly metabolized at the splanchnic level stimulate renal hemodynamics less than those which are rapidly transaminated and deaminated in the liver (serine, proline, alanine, dicarboxylic acids and the gluconeogenetic AA in general) [2,[3][4][5]. Moreover, glucagon has been repeatedly proposed as an important element in AA-induced renal hyperfiltration [3,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This observation is in agreement with the study of Premen and Dobbins, 22 who have shown that amino acid combinations of L-but not r>isomers elevated RPF and GFR, and with Castellino et al, 23 who demonstrated that RPF and GFR were increased by a solution of gluconeogenic amino acids containing L-arginine. NO may have taken part in the renal hemodynamic response to amino acids in our patients during a normal salt diet.…”
supporting
confidence: 92%
“…In contrast, glucagon infusion increasing plasma concentration to 900 pg/ ml or above (5) (a concentration usually achieved in the portal circulation) or infusion of lower amounts in the portal vein (10) does increase GFR. It has been proposed that the rise in GFR could depend on the liberation by the liver of a mediator or metabolite derived from amino acid metabolism (6,15,16,21). A putative liver-derived vasoactive mediator glomerulopressin has not been well characterized to date (for review see reference 20).…”
Section: Groups Plasma Urea (Mm)mentioning
confidence: 99%
“…It has been proposed that glucagon could induce the release from the liver of a vasoactive hormone, glomerulopressin, influencing the resistance of renal arterioles (17,18, and for reviews see references 19 and 20). Other studies have suggested that the link between the liver and the kidney could be a compound(s) derived from the metabolism of amino acids by the liver (21)(22)(23). The nature of this compound has not yet been determined.…”
Section: Introductionmentioning
confidence: 99%